Korupsi APD Covid-19: Tantangan Penegakan Hukum Administrasi Negara dalam Mewujudkan Transparansi dan Akuntabilitas Publik - Yuni Putri Dewantara; Dave David Tedjokusumo; Agustin Widjiastuti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Corruption in Indonesia is a serious problem that affects various aspects of people's lives and the stability of the country. This research discusses the impact of corruption on government administration with a focus on the Covid-19 personal protective equipment (PPE) procurement case involving the former Head of the North Sumatra Health Service, Alwi Mujahit Hasibuan. This case reflects a violation of the principles of transparency and accountability in the State Administrative Law (HAN), showing that the implementation of this law still faces many challenges. This research evaluates how weaknesses in monitoring and control mechanisms can lead to significant state losses and a decline in public trust. The research results reveal the need to strengthen HAN, increase supervision and accountability, as well as continuous education and training for public officials. In addition, strict law enforcement and improving the goods and services procurement system are very important to prevent corrupt practices in the future. With in-depth reform and consistent implementation, it is hoped that Indonesia can face the challenge of corruption more effectively, create a more transparent and accountable government, and increase public trust in government institutions.